Dynamics of the biodiversity of black and white cattle influenced by cross-breeding - N. A. Zinovieva; E. A. Gladyr; V. A. Bagirov; G. Brem (Вавиловский журнал генетики и селекции, 2015)
The inter-breed crossing (crossbreeding) permits one to introduce new alleles, extend genetic diversity, and achieve desired phenotypic characteristics of initial breeds. On the other hand, crossbreeding may cause a decrease in genetic differentiation of indigenous breeds due to loss of the part of their unique allele pool. The objective of the present work was to investigate the effect of crossbreeding on the allele pool variability of Russian Black and White cattle by using 10 microsatellite loci (BM1818, BM2113, ETH10, ETH225, TGLA122, TGLA126, TGLA227, ILST005, ETH185, and ILST006). The study was performed with purebred pedigree bulls of the Russian Black and White breed (BW_PB, n = 14) and two groups of their crosses with Holsteins carrying 25,0–62,5 % (BW_KR1, n = 16) and less than 12,5 % of the Black and White gene pool (BW_KR2, n = 67). Purebred Holstein bulls (HOLST, n = 42) were used as a reference group. It was found that the increase in Holstein’s blood could lead to the observed decrease in genetic diversity evaluated by the average number of effective alleles per loci (from 4,59 ± 0,46 to 3,87 ± 0,53), by the value of the Shannon index (from 1,60 ± 0,13 to 1,46 ± 0,14) and by the observed heterozygosity degree (from 0,779 ± 0,053 to 0,687 ± 0,055). It is shown that crossbreeding with Holsteins increases the genetic similarity to HOLST: Fst = 0,058, 0,036, and 0,026; Rst = 0,088, 0,060, and 0,050; DNei = 0,306, 0,178, and 0,123 for BW_PB, BW_KR1, and BW_KR2, respectively. Decrease in the genetic difference between the Black and White breed and Holsteins due to crossbreeding is confirmed by cluster analysis. Thus, evaluation of the allele pool and the level of genetic variability in populations are necessary for the efficient management of farm animal genetic recourses.